69 DISRUPTION OF VASCULAR ENDOTHELIAL GROWTH FACTOR SIGNALING CAUSES PULMONARY HYPERTENSION AND DECREASED LUNG GROWTH IN THE NEWBORN BUT NOT THE ADULT RAT. (1st January 2005) - Vaughn, R. C.; Abman, S. H.; Balasubramiam, V.; Markham, N.; Maxey, A.
Abstract : Neonatal pulmonary hypertension is associated with high levels morbidity and mortality. Vascular endothelial growth factor (VEGF) stimulates vessel growth and decreased VEGF activity also plays a role in the development of pulmonary hypertension. Previous studies suggest that VEGF may play an especially critical role in maintaining normal lung vascular growth and function during development than in adult life. Based on these studies we hypothesize that disruption of VEGF signaling will cause pulmonary hypertension and impair lung growth in the newborn but not the adult. To test this hypothesis, we treated 30 newborn Sprague-Dawley rats and 15 adult Sprague-Dawley rats with a single dose of the VEGF receptor inhibitor SU5416 (20mg/kg SQ). At two weeks, we measured right ventricular hypertrophy (RVH) by determining the ratio of right ventricle to the left ventricle plus septum (RV/LV+S) and performed morphometric analysis by measuring radial alveolar counts (RAC) as a marker of alveolarization. We found that SU5416 treatment caused marked increase in RVH in neonatal rats, from 0.271±0.141 to 0.409±0.189 (p≤0.01). In contrast, SU5416 treatment of adult rats did not cause RVH. By mophometric analysis, SU5416 treatment of newborn rats reduced RAC by 62.2% from 12.500±1.628 to 7.778±0.434 (p≤0.05). RAC was not affected by SU5416 treatment of adult rats. We conclude that SU5416 causes pulmonary hypertension and decreased alveolarization in neonatal, but not adult rats. Based on these findings, we speculate that VEGF signaling plays a critical role in stimulating and maintaining vessel growth in the developing lung, especially in comparison with the adult lung. We further speculate that early disruption of VEGF can cause long lasting cardiovascular damage.